2015
DOI: 10.1111/jpi.12292
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective and anti‐apoptotic effects of melatonin on hemolytic hyperbilirubinemia‐induced oxidative brain damage

Abstract: Melatonin exerts protection in several inflammatory and neurodegenerative disorders. To investigate the neuroprotective effects of melatonin in an experimental hemolysis-induced hyperbilirubinemia, newborn Sprague-Dawley rats (25-40 g, n = 72) were injected with phenylhydrazine hydrochloride (PHZ; 75 mg/kg) and the injections were repeated at the 24th hour. Rats were treated with saline or melatonin (10 mg/kg) 30 min before the first and second PHZ injections and 24 h after the 2nd PHZ injections. Control rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 71 publications
2
43
0
Order By: Relevance
“…The increase in apoptotic cells in the hippocampus of the PHZ group was ameliorated by melatonin treatment. These studies validate melatonin's role in neuroprotection and antiapoptosis in oxidative-related neuronal injury [41].…”
Section: Effect Of Melatonin On Hypersomnolencementioning
confidence: 55%
“…The increase in apoptotic cells in the hippocampus of the PHZ group was ameliorated by melatonin treatment. These studies validate melatonin's role in neuroprotection and antiapoptosis in oxidative-related neuronal injury [41].…”
Section: Effect Of Melatonin On Hypersomnolencementioning
confidence: 55%
“…Accordingly, it has been identified that BDNF/CREB pathway is suppressed in AD brain as well as at the neurons treated with Aβ . Besides, melatonin can attenuate the downregulation of BDNF and protect against neuronal apoptotic during brain damage in rats . Thus, we propose that melatonin might rescue Aβ‐induced neurotoxicity via increasing the level of BDNF and elevating the expression of miR‐132 correspondingly.…”
Section: Discussionmentioning
confidence: 86%
“…could also reduce the injuries in both gray and white matter and better the neurobehavioral outcomes induced by transient focal cerebral ischemia as a potent radical scavenger [296]. Furthermore, melatonin (10 mg/kg) was found to exhibit the neuroprotective and anti-apoptotic effects on oxidative brain damage induced by hemolytic hyperbilirubinemia in newborn Sprague-Dawley rats by reversing the increased plasma TNF-α, IL-1β levels, as well as the decreased brain derived neurotrophic factor (BDNF), S100 calcium-binding protein B (S100B) and IL-10 values [297]. …”
Section: Bioactivities Of Melatoninmentioning
confidence: 99%